A comparative study of drug prescribing indicators in various hospitals of West Bengal, India - Ghosh, Arijit; Adhikari, Anjan; Indu, Rania; Ghosh, Srijita; Banik, Santosh; Paul, Subhajit (International Journal of Research in Medical Sciences, 2018)
Background: Rational use of drugs is essential to ensure safety and welfare of patients. Thus, prescription audits are conducted to monitor the practice of writing prescriptions. Various standard parameters have been rationalized by World Health Organization (WHO) in order to regulate drug utilization, globally. Present study aimed to compare the pattern of prescriptions generated in different healthcare centres of West Bengal. Methods: A cross-sectional study was conducted in the inpatient and outpatient departments of RG Kar Medical College, Kolkata, in order to evaluate the prescriptions. Literature was also surveyed with the keywords “prescription audit”, “West Bengal”, to extract data on prescription audits conducted in various other hospitals of West Bengal. The WHO prescribing indicators of all these health facilities were then compared to estimate the rationality of drug prescribed by different physicians. Results: Seven published reports of prescription audits were published from the period of 2013 to 2017, the distribution being- 2 health facilities from Kolkata, 2 from Burdwan, 1 each from Bankura, Murshidabad and North Bengal. WHO standards were not strictly followed by any of the hospitals. Polypharmacy level were higher in all the hospitals. Drugs were mostly prescribed from the essential medicine list (EML). Conclusions: Present study clearly indicated that it is essential to improve these parameters for most of the healthcare centres in order to prevent irrational use of drugs. Prescription audits should also be implemented regularly so that the patients can receive better treatment at minimum cost with suitable rational therapy.